Yemen: cholera outbreak and the ongoing armed conflict - Dureab, Fekri; Jahn, Albrecht (Journal of infection in developing countries, 2018)
Yemen was affected by a major cholera epidemic in 2016, while a civil war, which has devastated the country since March 2015, has exacerbated the humanitarian situation. Cholera is a disease caused by the bacterium Vibrio cholera, thus this study aims to analyze the epidemiological features of the outbreak and explore the relation of the outbreak to the current armed conflict situation. The data were obtained from the national surveillance system in Yemen. This contains details of 15,074 cases registered as suspected cholera patients per governorate from week 39 to 52 in 2016. In addition to the data concerning cholera, other data on conflict-related injuries, and population movement (numbers of Internally Displaced Persons - IDPs - and number of displaced returnees) were used to assess the correlation using Spearman's rho analysis. The data analysis shows the intensity of the conflict as measured by the total casualties per governorate (conflict-related injuries and death) is significantly correlated with the number of cholera cases per governorate (r 0.483, P = 0.026). The analysis also shows a positive, but not significant correlation between cholera cases, and both the number of conflict internal displaced people (IDPs) (r 0.389, P = 0.081), and number of returnees (r = 432, P = 0.050).